Melt processable polyacrylonitrile copolymer precursors for carbon fibers: Rheological, thermal, and mechanical properties - Lee, Jae Hyeok; Jin, Jeong-Un; Park, Sejoon; Choi, Dalsu; You, Nam-Ho; Chung, Yongsik; Ku, Bon-Cheol; Yeo, Hyeonuk (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
•Poly(acrylonitrile-co-methylacrylate) was synthesized as a melt processible carbon fiber precursor.•Thermal and rheological analysis confirmed flow characteristics suitable for melt-spinning.•The precursor fibers were thermally stabilized by assistance of electron-beam irradiation without re-melting and fusion.•The mechanical properties of resulting-carbon fiber were 1.37GPa in tensile strength and 110GPa in modulus, respectively. Polyacrylonitrile (PAN) copolymers containing varying amounts of methyl acrylate (MA), P(AN-co-MA), were synthesized as a melt-spinnable precursor of carbon fibers. The rheological properties of P(AN-co-MA) with MA content of 15mol% at 190°C proved to be suitable for melt-spinning and the PAN fiber was spun from an extruder. In order to prevent remelting and fusion of the fibers in the stabilization process, electron-beam irradiation of over 1500kGy was used and the melt-spun PAN fibers were successfully converted to stabilized PAN fibers by thermal treatment up to 250°C. Finally, carbon fibers (CFs) were produced by pyrolysis of the stabilized PAN fibers. The mechanical properties of the resulting-CFs were evaluated; the tensile strength, tensile modulus, and elongation at break were 1.37±0.2GPa, 110±11.1GPa, and 1.27±0.28%, respectively. These results suggest the possibility of utilizing melt-spinning as a cost-efficient method for fabrication of carbon fibers.